Influence of metabolic syndrome on left atrial size among sample of patients attending Al Karama teaching hospital in Iraq - Dhaidan, Fuad Abdullah (International Journal of Research in Medical Sciences, 2018)
Background: Left atrial (LA) enlargement has been linked to obesity and insulin-resistance in adults. The aim of this study was to determine the association between LA area and: a) different components of the metabolic syndrome including obesity (OB) measures of body mass index (BMI) and waist circumference (WC)), insulin resistance (IR, proinsulin), and blood pressure (BP) b) left ventricular mass and diastolic function measured by echo doppler. Methods: 90 subjects, (42 OB (BMI >30, 30, overweight (BMI >25)), 18 non-OB (BMI <25. BMI, WC, BP, tanner stage, and mode M, 2-dimensional and doppler transmitral echocardiography were assessed. A standard oral glucose tolerance test (OGTT) was done, measuring glucose, insulin, and proinsulin concentrations. Results: Hypertension was only present in OB (30%). LA enlargement (>2 SD) adjusted for height was more frequent in OB and overweight. Significant univariate association (P<0.001) was found between LA area and height (r = 0.52), age (r = 0.45), tanner stage(r = 0.45), BMI (r = 0.66), WC (r = 0.70), systolic BP (r = 0.52), diastolic BP (r =0.53), proinsulin (r = 0.36) and HOMA-IR (r = 0.36). In the multivariate regression analysis, independent variables were entered in a stepwise fashion: initially, gender (P = 0.006), and tanner stage (P = 0.011) were still significant independent correlates of LA area after adjusting for age, gender, and Tanner stage. Subsequently incorporation of WC showed that WC (P = 0.018) was a significant independent correlate of LA area. A regression model constructed to test the significance of adjustment factors, including WC, BP, left ventricular mass, and HOMA-IR showed that WC (P<0.001) was the only significant independent variable. Conclusions: Waist circumference is the main factor affecting left atrial size among patient with metabolic syndrome.